Mechanical compressor-driven thermochemical storage for cooling applications in tropical insular regions. (December 2017) - Ferrucci, Franco; Stitou, Driss; Ortega, Pascal; Lucas, Franck
Abstract: The energy situation in tropical insular regions, such as in the French Polynesian islands, presents a number of challenges, including high dependence on imported fuel, high transport costs from the mainland and weak electricity grids. With regards to electrical energy demand, the high temperatures in these regions throughout the entire year implies that a large proportion of electricity consumption (~40%) is used to cool buildings, even during evening hours. This paper presents an air conditioning system driven by photovoltaic (PV) electricity that combines a mechanical vapor refrigeration system and a thermochemical storage unit. Thermochemical processes are able to store energy in the form of chemical potential with virtually no losses, and this energy can be used to produce cooling during the evening hours without the need to run a compressor. The efficiency of such a hybrid system is evaluated and compared with alternative processes that utilize either electrochemical (Pb, Li-ion batteries) or thermal storage (ice, chilled water) for cooling production.